Apakah Mengembalikan Hadiah Hasil Kejahatan, Meniadakan Proses Penyidikan? (Analisis Kasus penerima hadiah Doni Salmanan) - Ichsan Syaidiqi; Latipah Nasution (ADALAH, 2022)
Since the discovery of the fraudulent investment case carried out by Doni Salmanan, law enforcement officers then confiscated the financial assets involved in the case. In addition to the ownership of luxury homes, financial assets in banks, to gifts that were given to a number of public figures. There were also several public figures who then voluntarily returned the gifts to police investigators, but the question arose as to whether returning the items could abolish the ongoing legal process. This paper tries to examine these events from the perspective of criminal law theory, law enforcement, and jurisprudence. Then it was found that returning the goods/gifts resulting from a crime does not necessarily negate or abolish the ongoing legal process, but it can be considered by the judge in deciding the case. In addition, for gifts that are still in the possession of the recipient of the gift, it is possible that the gift will be confiscated by investigators for the sake of investigation.